Eruption of Mt. Pinatubo and climate of Syowa Station - Susumu Kaneto (National Institute of Polar Research, 1997)
During the last year of the Antarctic Climate Research (ACR) period, two large volcanos erupted. In June 1991,the volcano Pinatubo in the Philippines Islands (15°N, 120°E) erupted and injected a large volcanic cloud in to the lower and middle stratosphere. In August 1991,Mt. Hudson in southern Chile (46°S, 73°W) erupted; its volcanic cloud reached to 18km. From NOAA/AVHRR data, within 1991,the volcanic aerosol of Pinatubo dispersed mainly in tropical latitudes and that of Hudson spread in the area south of 40°S. The eruption effects are investigated here by comparing meteorological observation results at Syowa Station (69°S, 39°E) with global analyses. The optical observations which measure direct effects of eruption materials, show a large effect from late 1991. Abnormal deviations were detected in surface temperature and total ozone amount but the occurrence is retarded relative to global average occurrence. Effects on stratospheric temperature were not detected.